Perspectives on economics and management : essays in honour of Anindya Sen - Ghosh, Saibal; Ray, Partha (Routledge, 2025)
"The world of economics and management is being reshaped in more ways than one including rapid advancements in technology and business practices. This book weaves together a diverse set of issues such as consumption patterns, wealth disparities and the management, behaviour and financial health of businesses and consumers to analyse the effectiveness of economic and business strategies. Rapid technological advancements along with the need for cost-effectiveness and convenience are making service providers embrace technology as a partner rather than a tool in their economic journey. Relatedly, traditional management philosophy is coming under a scanner, with an increasing emphasis on holistic development of the organization, rather than a top-down approach, as has been the case in the past. Understanding major developments in economic and financial policymaking has perennially been a key concern of public policy, shaped by recent global and related developments, this has necessitated a relook at these issues, couched in a cross-cutting perspective. Viewed from this standpoint, the present volume, written to honour the rich academic work of the eminent economist Professor Anindya Sen intersects this triad of economics, finance and public policy that are integral to policy thinking and its formulation. The smorgasbord of research ideas, involving both theoretical analysis and empirical evidence, presented in this volume, provides useful perspectives on the drivers that are continually reshaping the dynamism in the world around us and, in the process, integrates a multidisciplinary perspective of focusing on several pertinent policy challenges. This book will be useful to researchers and students of economics, finance and public policy, economic theorists, microeconomics, and even to those with a broader canvass such as researchers in macroeconomics, international economics, business, management and marketing"-- Provided by publisher.
Keywords: Managerial economics.; Management.; Economics.; elektronické knihy; electronic books